Curriculum Development of Tahfidz Al-Quran Full Day School System: A case in Indonesian Context - Nailatul Muna (Tadibia Islamika, 2022)
This study aims to determine the implementation of the development of the Tahfidz al-Quran curriculum with a full-day school system at SDQ Anwarul Muhlasin Magelang. One of the efforts made by the world of education to meet the expected needs is the existence of various models of formal education ranging from international school-based schools, full-day schools, boarding schools and other school models. This research is descriptive qualitative research. In data collection, the techniques used are interviews, observation, and documentation. Data analysis techniques through data reduction, data presentation and verification. The results of the study are (1) SDQ Anwarul Mukhlasin is a full-day school-based school that has a special characteristic, namely Tahfidz Al-Qur'an with the application of a curriculum that combines the national curriculum and the local content curriculum of Islamic boarding schools that insert the values of the Tablighi Jama'ah teachings (2) Anwarul Muhlasin SDQ curriculum development includes needs diagnosis, formulation of educational goals, selection of content organizations, selection of learning experience organizations, and evaluation.